An interesting cause of a buccal swelling- Long buccal Schwannoma: A case report - I. Puri; T. Wildan; M. Amin (Elsevier, 2022)
Schwannomas are the most common type of benign peripheral nerve sheath tumour and usually occur as a slow-growing, solitary, encapsulated mass. Schwannomas of the oral cavity are rare, with the commonest sites being the tongue, palate and floor of mouth. We present the case of a 28-year-old male patient who presented with a left buccal swelling and pain. Radiological investigation and incisional biopsy led to a diagnosis of a Schwannoma associated with the left long buccal nerve, which was fully excised with no complications.